Free prostate-specific antigen, total prostate-specific antigen, and their ratio associated with diabetic kidney disease: new evidence from male patients with diabetes in the United States - Limei Zhang; Chengxia Li; Deying Niu; Shihua Zhao (European Journal of Medical Research)
Abstract Objectives To examine the associations between prostate-specific antigen (PSA)-related biomarkers and diabetic kidney disease (DKD) in male patients with diabetes. Methods This study utilized data from the National Health and Nutrition Examination Survey (NHANES) conducted between 2001 and 2010, including 1,681 male diabetic patients (409 of whom had DKD). Multivariable logistic regression models adjusted for age, race, body mass index (BMI), hypertension, and cardiovascular disease were employed to evaluate the relationships between total PSA (TPSA), free PSA (FPSA), and the FPSA/TPSA ratio with DKD. Dose–response curves and subgroup analyses were performed to further assess these associations. Results Elevated levels of TPSA, FPSA, and the FPSA/TPSA ratio were significantly associated with an increased risk of DKD. In fully adjusted models, the highest tertiles of TPSA (OR = 1.92, 95% CI 1.43–2.56) and FPSA (OR = 2.69, 95% CI 2.00–3.60) demonstrated the strongest associations. The FPSA/TPSA ratio exhibited a linear dose–response relationship with DKD (OR = 2.16, 95% CI 1.60–2.91), whereas TPSA and FPSA showed non-linear threshold effects. Subgroup analyses confirmed consistent findings across populations. Conclusions PSA-related biomarkers may serve as potential indicators for early diagnosis and risk stratification of DKD. Further validation studies and mechanistic investigations are necessary to optimize clinical interventions and improve renal outcomes in diabetic patients.